Perceived Level of Effects of Gamification and Student Engagement of Senior High School Students - Casia, Candace Nathalie; Angga, Carl Joseph; Bayron, Luke Carlyle; Caralos, Aljean Nicolle; Guinto, Eshly Jodah; Iligan , Jasmine Samantha; Lunasin, Kim; Palacio, Ira; Tampus, Stephanie; Goc-Ong, Marie Vi (Journal of Interdisciplinary Perspectives, 2024)
This study investigated the impact of gamification on student engagement and learning outcomes among grade 11 students. Specifically, it examined the relationship between the perceived effects of gamification and student engagement. A non-experimental quantitative research design with a descriptive correlational method was employed, involving 76 senior high school students from a medical school in Davao City. Data were collected using modified versions of the "Gamification and Learning Engagement Questionnaire" (GLEQ) and the "Student Course Engagement Questionnaire" (SCEQ). Results indicated high mean scores for both the effects of gamification and student engagement, with a significant positive correlation between the two variables. This suggests that gamification can significantly enhance learning outcomes by creating an engaging and dynamic learning environment. The study highlights the potential of gamification to foster student engagement, encouraging instructors to integrate game-like elements and activities into their teaching. Teachers can increase student interest and improve classroom performance by adopting various gamified strategies.